A crosslinguistic study of reduplication - Nadarajan, Shanthi (Second Language Acquisition and Teaching (SLAT), 2006)
Reduplication is an important phenomenon in language studies. Its linguistic forms has long been studied in terms of various formalist theories but there is a general consensus that the role of reduplication in English has been widely ignored. Recent corpus based studies have indicated that the usage of reduplication among English speakers is more widespread than assumed to be and needs in depth study. This article takes another look at the traditional forms of reduplication and current views on how they occur. It also discusses reduplication and repetition found in Malay and Tamil and compares them with English forms, in order to establish a pattern.